Chronic Disability Determination After Work-Related Mild Traumatic Brain Injury. Issue 3 (May 2015) - Carone, Dominic A.; Bell, Jeneita M.; Taylor, Christopher A.; Breiding, Matthew J.; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Case scenario: A middle aged man suffered a mild traumatic brain injury (MTBI) at work due to a fall. The diagnosis of MTBI was based solely on self-reported altered mental status.1 All neuroimaging results and neurological examination findings were negative in the acute and chronic phases. There was no other history of MTBI or neurological condition. The patient had been out of work since the injury (1 year ago) and received wage replacement benefits through a Workers' Compensation company. An attorney was assisting the patient with Workers' Compensation proceedings, settlement negotiations, and possible civil litigation. The patient had been evaluated in clinical settings by multiple doctoral and nondoctoral level healthcare providers. Upon the patient's request, all healthcare providers signed disability forms attesting to disability (50%-100%). The disability determinations were based primarily on self-report and, in some cases, were influenced by behavioral observations (eg, crying) but not by objective examination findings. The patient was held out of work for more than a year despite neuropsychological testing results showing unequivocal evidence of exaggeration and/or malingering. The patient went to a Workers' Compensation hearing and was told that for benefits to continue, the disability rating must be 100% from all providers. The patient contacted the healthcare provider(s) who provided a 50% disability rating and informed them of this. Without any further evaluation, and based purely on the phone call, written documentation was provided on the same day declaring that the patient was 100% (totally) disabled. Per standard Workers' Compensation language, the disability note also stated that the patient's complaints were consistent with his or her history of the injury.